2015
DOI: 10.1021/pr5013015
|View full text |Cite
|
Sign up to set email alerts
|

Host–Pathogen Interaction Profiling Using Self-Assembling Human Protein Arrays

Abstract: Host-pathogen protein interactions are fundamental to every microbial infection, yet their identification has remained challenging due to the lack of simple detection tools that avoid abundance biases while providing an open format for experimental modifications. Here, we applied the Nucleic Acid-Programmable Protein Array and a HaloTag-Halo ligand detection system to determine the interaction network of Legionella pneumophila effectors (SidM and LidA) with 10,000 unique human proteins. We identified known tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 64 publications
1
56
0
Order By: Relevance
“…Regrettably, their lack of solubility and their necessity of remaining in lipid-rich environment highly impairs their interactome mapping via conventional methods such as AP-MS. To overcome these challenges, Glick Y et al introduced a screening method for HP interactions, adequate for transmembrane proteins [62] named the human Membrane Protein Array (MPA). Similarly, several studies have developed and applied Protein Micro Array technologies [63] including Nucleic Acid Programmable [64] or AVEXIS (AVidity-based Extracellular Interaction Screen) [65,66] to study soluble and transmembrane HP interactions (see supplementary table 1). …”
Section: Protein-protein Interactions Detection Methodsmentioning
confidence: 99%
“…Regrettably, their lack of solubility and their necessity of remaining in lipid-rich environment highly impairs their interactome mapping via conventional methods such as AP-MS. To overcome these challenges, Glick Y et al introduced a screening method for HP interactions, adequate for transmembrane proteins [62] named the human Membrane Protein Array (MPA). Similarly, several studies have developed and applied Protein Micro Array technologies [63] including Nucleic Acid Programmable [64] or AVEXIS (AVidity-based Extracellular Interaction Screen) [65,66] to study soluble and transmembrane HP interactions (see supplementary table 1). …”
Section: Protein-protein Interactions Detection Methodsmentioning
confidence: 99%
“…In addition, insufficient or biased coverage of the screened host cell proteome can impede these approaches. Recently, nucleic acid programmable protein arrays (NAPPA), which rely on in vitro transcription and translation to allow the profiling of effector interaction partners on self-assembling protein arrays, have been introduced (Yu et al 2015). These promise to provide a straightforward way of screening around 10 000 host cell proteins for interaction with an effector without the need of purifying the effector and host cell proteins.…”
Section: Assessing Effector Function By Identifying Host Cell Interacmentioning
confidence: 99%
“…6C). A chemical reporter for protein AMPylation has been successfully employed to profile target proteins of SidM, the Vibrio parahaemolyticus effector VopS and the human protein HYPE (Grammel et al 2011;Bunney et al 2014;Yu et al 2015). In addition, metabolic labelling of host cells with substrate analogues can also reveal the PTM of effectors by host cell enzymes.…”
Section: Functionalized Substrate Analogues To Profile Ptmsmentioning
confidence: 99%
“…For example, N6-pATP can be used with recombinant AMPylators to identify potential substrates in whole cell lysates [48•]. To complement profiling of cell lysates, N6-pATP and recombinant AMPylators can also be used with n ucleic a cid- p rogrammable p rotein a rrays (NAPPA) to identify candidate substrates in vitro [49•,50•]. These studies have revealed new candidate GTPase and non-GTPase substrates for the secreted bacterial effectors VopS and IbpA [49•].…”
Section: Ampylationmentioning
confidence: 99%